A Longitudinal Field Study of Auto-GCAS Acceptance and Trust: First-Year Results and Implications. (September 2017) - Ho, Nhut; Sadler, Garrett G.; Hoffmann, Lauren C.; Zemlicka, Kevin; Lyons, Joseph; Fergueson, William; Richardson, Casey; Cacanindin, Artemio; Cals, Samantha; Wilkins, Mark
In this paper we describe results from the first year of field study examining U.S. Air Force (USAF) F-16 pilots' trust of the Automatic Ground Collision Avoidance System (Auto-GCAS). Using semistructured interviews focusing on opinion development and evolution, system transparency and understanding, the pilot–vehicle interface, stories and reputation, usability, and the impact on behavior, we identified factors positively and negatively influencing trust with data analysis methods based in grounded theory. Overall, Auto-GCAS is an effective life-/aircraft-saving technology and is generally well received and trusted appropriately, with trust evolving based on factors including having a healthy skepticism of the system, attributing system faults to hardware problems, and having trust informed by reliable performance (e.g., lives saved). Unanticipated findings included pilots reporting reputation to not be negatively affected by system activations and an interface anticipation cue having the potential to change operational flight behavior. We discuss emergent research avenues in areas of transparency and culture, and values of conducting trust research with operators of real-world systems having high levels of autonomy.